2015
DOI: 10.1007/s11306-015-0829-0
|View full text |Cite
|
Sign up to set email alerts
|

Gender-specific pathway differences in the human serum metabolome

Abstract: The susceptibility for various diseases as well as the response to treatments differ considerably between men and women. As a basis for a gender-specific personalized healthcare, an extensive characterization of the molecular differences between the two genders is required. In the present study, we conducted a large-scale metabolomics analysis of 507 metabolic markers measured in serum of 1756 participants from the German KORA F4 study (903 females and 853 males). One-third of the metabolites show significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
205
2
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 237 publications
(244 citation statements)
references
References 73 publications
33
205
2
4
Order By: Relevance
“…This suggests that men, more than women, may utilize endogenous protein catabolism to provide substrates for the TCA cycle. Sex-specific differences in metabolism have been demonstrated, and may be operative in ME/CFS patients, involving fatty acids, amino acids, oxidative phosphorylation, and steroid metabolism (33). In contrast to the sex-specific effects on serum amino acids, the increased expression of PDKs and PPARD (mRNA in PBMCs) was similar in women and men with ME/CFS.…”
Section: Discussionmentioning
confidence: 97%
“…This suggests that men, more than women, may utilize endogenous protein catabolism to provide substrates for the TCA cycle. Sex-specific differences in metabolism have been demonstrated, and may be operative in ME/CFS patients, involving fatty acids, amino acids, oxidative phosphorylation, and steroid metabolism (33). In contrast to the sex-specific effects on serum amino acids, the increased expression of PDKs and PPARD (mRNA in PBMCs) was similar in women and men with ME/CFS.…”
Section: Discussionmentioning
confidence: 97%
“…This is, in part, due to the fact that sex hormones regulate mitochondrial function and biogenesis (Gaignard et al, 2017). Metabolomic signatures also, which indirectly reflect mitochondrial and cellular metabolism of the whole organism, show that up to one-third of metabolites at baseline differ between women and men (Krumsiek et al, 2015). In relation to stress, a recent meta-analysis of the literature on the effects of induced stress on mitochondrial structure and function revealed that all studies to date have been conducted in male rodents (Picard and McEwen, 2018b).…”
Section: Sexual Dimorphism In Mitochondria and Stress Physiologymentioning
confidence: 99%
“…The reasons for the different metabolite concentrations are not always known. In case of glycine, it could be due to genetic polymorphisms [12,15,17], in case of citrate it is largely speculative. Since a further intermediate of the citrate cycle, α-ketoglutaric acid, is also higher in women [13,16,18,19,47,51,52], this may hint at a general difference in citrate cycle turnover between men and women.…”
Section: Discussionmentioning
confidence: 99%
“…The calculation of the metabolite patterns of REE and LBM for men and women separately showed no meaningful results. It is known from other studies that age and sex differences exist in the human plasma and urine metabolome [12][13][14][15][16][17][18]. Nevertheless, if and to which extent the discrimination of sex is responsible for the discrimination of body composition, has not been clarified definitely [20][21][22][23].…”
Section: Metabolite Profiles Of Lean Body Mass In Plasma and Urinementioning
confidence: 99%
See 1 more Smart Citation